KAJIAN FITOGEOGRAFI TUMBUHAN ANGGREK ENDEMIK DI HUTAN PENELITIAN UNIVERSITAS BORNEO TARAKAN - Kurniwati Kurniwati; Ibrahim Ibrahim; Fitri Wiyarini (Biopedagogia, 2022)
The purpose of this study is to examine the phytogeography of endemic orchid plants in the University of Borneo Tarakan research forest. In this sort of exploratory research, the sampling point is chosen by the researcher using an adaptive sampling sample. This study was conducted in the University of Borneo Tarakan’s Research Forest, which has an area of around 70 ha. The sample site has a 120,617 m² location area. According to the study’s findings, there are two different species of orchids, including Bromhedia finlaysoniana, which has a terrestrial habitat, and Dendrobium crumenatum, which has an epiphytic habitat. From the results of these values, the average distribution value is 1, which means that the distribution pattern is random. Orchid growth can also be affected by different environmental parameters in each location.  Bromhedia finlaysoniana and Dendrobium crumenatum, two types of orchids that were discovered as a result of the research, are endemic to tropical southeast Asian countries and are common in many regions of Indonesia, including Kalimantan, Maluku, java, the Lesser Sunda Islands, Sulawasi, and Sumatra.  Keywords:  phytogeography study, Bromheadia finlaysoniana, Dendrobium crumenatu, Endemic